2012
DOI: 10.1073/pnas.1113512109
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for mutual relief of the Rac guanine nucleotide exchange factor DOCK2 and its partner ELMO1 from their autoinhibited forms

Abstract: DOCK2, a hematopoietic cell-specific, atypical guanine nucleotide exchange factor, controls lymphocyte migration through ras-related C3 botulinum toxin substrate (Rac) activation. Dedicator of cytokinesis 2-engulfment and cell motility protein 1 (DOCK2•ELMO1) complex formation is required for DOCK2-mediated Rac signaling. In this study, we identified the N-terminal 177-residue fragment and the C-terminal 196-residue fragment of human DOCK2 and ELMO1, respectively, as the mutual binding regions, and solved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 31 publications
(49 reference statements)
6
71
0
Order By: Relevance
“…Excluding redundant sequences, >200 PH‐like domain structures have been solved. Structures have confirmed earlier identifications made solely on the basis of remote sequence homology in most31, 32 but not all33 cases.…”
Section: Defining a Ph‐like Domainsupporting
confidence: 82%
“…Excluding redundant sequences, >200 PH‐like domain structures have been solved. Structures have confirmed earlier identifications made solely on the basis of remote sequence homology in most31, 32 but not all33 cases.…”
Section: Defining a Ph‐like Domainsupporting
confidence: 82%
“…The question raised is how the same domain mediates the interaction of Elmo2 with both proteins? Studies of the interaction between Elmo and Dock protein revealed that the aPH domain does not directly contact with Dock, but provides a structural determinant in that the helice (␣N and ␣C) before and after the PH domain along the PXXP motif were arranged to direct contact with Dock protein (35,38). In our studies, we found that the aPH domain without these helices was sufficient to interact with ClipR-59 (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…The Interaction between ClipR-59 and Elmo2 Enhances the Levels of Active Rac1-Elmo2 interacts with the Dock family protein to activate downstream targets including Rac1 (35). To determine whether Elmo2, ClipR-59, and Dock protein forms a tertiary complex, a co-immunoprecipitation assay was carried out with COS-7 cell lysates that express FLAG-Dock180 alone or HA-ClipR-59 plus FLAG-Dock2, or HA-ClipR-59 plus FLAG-Dock180 and Myc-Elmo2, with anti-FLAG antibody.…”
Section: Clipr-59 Is Involved In Myoblastmentioning
confidence: 99%
“…Recent data suggest that Elmo and Dock2 may exist as individual autoinhibited proteins that form a complex following stimulation to relieve both proteins from their inhibited state (Fig. 3A [ii], B; Hanawa-Suetsugu et al 2012). The recruitment of the Elmo/Dock1 complex to the membrane is also guided by Elmo-interacting proteins (Fig.…”
Section: Elmo Scaffolds Orchestrate Dock-mediated Rac Activationmentioning
confidence: 99%